2001
DOI: 10.1128/jvi.75.3.1408-1413.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Prion Protein Regions That Modify Scrapie Incubation Time

Abstract: The prion diseases are an unusual group of fatal neurodegenerative disorders which include Creutzfeldt-Jakob disease, fatal familial insomnia, and Gerstmann-Sträussler-Scheinker disease in humans as well as bovine spongiform encephalopathy in cattle and scrapie in sheep and goats. A wealth of evidence supports the hypothesis that these diseases are caused by a conformational change in the prion protein (PrP) from its normal, cellular isoform (PrP C ) into a pathogenic, infectious isoform (PrP Sc ) (17,18,21). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
103
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 35 publications
(31 reference statements)
11
103
1
Order By: Relevance
“…2). Using the PTA precipitation method, we partially purified 301V prions from FVB mice and MoSP1 prions from transgenic (Tg) mice overexpressing MoPrP(89-231), designated Tg9949 mice (18). The 301V strain was derived from bovine spongiform encephalopathy prions passaged through mice (19).…”
Section: Prion-infected Brain Homogenates Can Seed Amyloid Formationmentioning
confidence: 99%
“…2). Using the PTA precipitation method, we partially purified 301V prions from FVB mice and MoSP1 prions from transgenic (Tg) mice overexpressing MoPrP(89-231), designated Tg9949 mice (18). The 301V strain was derived from bovine spongiform encephalopathy prions passaged through mice (19).…”
Section: Prion-infected Brain Homogenates Can Seed Amyloid Formationmentioning
confidence: 99%
“…1 A). At the N terminus, we found that HuM-E123, which recognizes the region of MoPrP (30)(31)(32)(33)(34)(35)(36)(37), bound weakly, and that HuM-E149, a HuM-Fab specific to the octarepeat region, bound even more weakly than HuM-E123 (Fig. 1 A).…”
Section: Immunochemical Characterization Of Wtmoprp-fc By Using Hum-fmentioning
confidence: 94%
“…The isolation of 301V (44), Me7 (45), RML (46), and synthetic prions (18) has been described. Tg9949 and Tg4053 mice have been described (47,48). CD-1 and FVB mice were purchased from Charles River Breeding Laboratories (Wilmington, MA).…”
Section: Methodsmentioning
confidence: 99%